Impact of high-yielding varieties on paddy production in Muda Agricultural Development Authority Areas, Malaysia - Adedoyin, Abiola Olapeju (2016)
Worldwide, technological change in paddy production has given in an era of agricultural development and increased productivity performance. However, such performance appears to be unevenly distributed among farmers. Though, with new technologies introduced in Malaysia, development is premised on the recognition that low productivity is a major cause of the lack of advancement in the paddy sector. Hence, in order to ensure self-sufficiency in paddy production, the use of high-yielding varieties of paddy seed has been a strategic way for increasing paddy yields. This study, therefore, investigated the impacts of high yielding varieties on paddy production in Muda Agricultural Development Authority, (MADA) Areas. Specifically, the study established whether the new high-yielding varieties have significant effects on paddy yield. The study also examined the magnitude of paddy production due to the shift from old to new HYVs of paddy seed. Furthermore, the study analyzed socio-economic factors influencing the adoption of new high yielding varieties as well as the optimum efficiency of resource used in paddy production. The data were collected through a well-structured questionnaire. The study sampled 396 paddy farmers using multistage sampling technique. The independent samples ttests, F-test, Cobb-Douglas production, Ordinary Least Square analysis technique and (binary) logit regression analysis were used to analyse the data. The estimated results of all the inputs used on per hectare had positive signs and conformed to a prior expectation. All the five inputs used, seed, fertilizer, labour, pesticides, and herbicides influence paddy yield in MADA, areas. The paddy farms were found to exhibit increasing return to scale. This shows that, the paddy farms have characteristics of stage one of production. It means that, if the farm increased all inputs by 1 per cent, production will give 1.07 per cent. This result obtained suggested that there is every possibility to increase paddy production by improving the use of those inputs. The findings re-affirmed the claim that socio-economic factors such as education level, farming experience, gender, training and farm size were the factors influencing the adoption of new high yielding varieties in MADA, areas. Estimated results on the effect of high-yielding varieties indicated that the use of the new high yielding varieties had a positive significant effect on paddy yield at 1 per cent. The result revealed 42 per cent more on average paddy yield by giving 1.5 times more yield compared to old varieties. There exists an upward neutral shift in production function curve. More so, since the coefficient of dummy is positively significant with a much smaller standard error of 0.02, the intercept of new high-yielding varieties is known to be higher than the old varieties which signify a shift in production function. Based on the estimated results on the optimum resource efficiency used in paddy production, it was revealed that all inputs employed, seed input, fertilizer application, pesticides, herbicide and labour inputs were under-utilized as their ratios were greater than unity. Therefore, maximum optimal resource achievement is possible by reorganizing input utilization allocation on paddy farms. The enhancement in the resource among the farmers is the work of the individual farmers, government and research institutions. It is therefore the responsibility of the extension agents to raise efficient and knowledge based paddy farmers through specific farm management training, which train the paddy farmers on the efficient use of available resources. This would help the farmers in allocating the inputs effectively. Extension agents in the study area as a whole also need to be improved on various ways used in disseminating new high yielding varieties to farmers. The strategies for paddy technology transfer to farmers should be specially packaged.